2020
DOI: 10.3233/shti200711
|View full text |Cite
|
Sign up to set email alerts
|

Do You Know Who Is Talking to Your Wearable Smartband?

Abstract: We study seven fitness trackers and their associated smartphone apps from a wide variety of manufacturers, and record who they are talking to. Our results suggest that some of them communicate with unexpected third parties, including social networks, advertisement websites, weather services, and various external APIs. This implies that such unanticipated third-parties may glean personal information of users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…(2017) successfully manipulated data on fitness tracking apps by injecting fabricated values in proof-of-concept attacks on wearable device platforms, exemplifying the vulnerability of these apps. Kazlouski et al. (2020) showed that fitness mobile apps contacted unexpected third parties (location services, advertisers and analytic providers), continuing to state that individuals are likely donating private information to device manufacturers in exchange to use the app.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…(2017) successfully manipulated data on fitness tracking apps by injecting fabricated values in proof-of-concept attacks on wearable device platforms, exemplifying the vulnerability of these apps. Kazlouski et al. (2020) showed that fitness mobile apps contacted unexpected third parties (location services, advertisers and analytic providers), continuing to state that individuals are likely donating private information to device manufacturers in exchange to use the app.…”
Section: Literature Reviewmentioning
confidence: 99%
“…platforms, exemplifying the vulnerability of these apps. Kazlouski et al (2020) showed that fitness mobile apps contacted unexpected third parties (location services, advertisers and analytic providers), continuing to state that individuals are likely donating private information to device manufacturers in exchange to use the app. Grundy et al (2017) validated privacy and security concerns related to prominent health apps by tracing the potential flow of consumers' data through network analysis, in which they identified a core of 15 app families through which data may travel.…”
Section: Integrated Fitness Appsmentioning
confidence: 99%
See 3 more Smart Citations